PENGEMBANGAN MEDIA PEMBELAJARAN PERMAINAN TRUTH AND DARE UNTUK MENINGKATKAN HASIL BELAJAR SISWA - Cintya Devi Ayunda Fanny (Edunomic : Jurnal Ilmiah Pendidikan Ekonomi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
AbstractThe limitations in the use of learning media in learning activities and the lack of student learning outcomes make researchers want to develop the learning media based on the Truth and Dare game as a learning medium on economic subjects in the APBN and APBD material. The research on development the learning media based on the Truth and Dare game aimed to explain the level of feasibility; analyzed effectiveness and practicality; the response of students to the learning media; and learning outcomes. This study uses the R&D method with the 4D Models research by Thiagarajan (define, design, develop, and disseminate.) The research subjects were 20 students of class XI social. Data collection techniques through interviews, questionnaires, and tests. Data analysis techniques are expert analysis and validation; student questionnaire responses; and gain score calculation. The learning media Truth and Dare game are considered very practical and effective so that they can improve student learning outcomes in accordance with the average N-Gain score of 0,71 with an increase in the pretest and postest scores with an excellent student response of 98,2%, percentage score of eligibility of 95,64%, percentage score of effectiveness of 100%, and percentage score of practicality of 100%. The learning media Truth and Dare game have also gone through the stages of review, revision, and validation with “very feasible”. Therefore, the learning media as a Truth and Dare game is very suitable for use in learning activities because it can improve student learning outcomes.Keywords : Media Learning, Truth and Dare game, Outcomes Learning